Risk factors of dysphagia in patients with ossification of the anterior longitudinal ligament. (12th October 2020) - Nishimura, Hirosuke; Endo, Kenji; Aihara, Takato; Murata, Kazuma; Suzuki, Hidekazu; Matsuoka, Yuji; Takamatsu, Taichiro; Maekawa, Asato; Sawaji, Yasunobu; Tsuji, Hanako; Yamamoto, Kengo
Introduction: Cervical ossification of the anterior longitudinal ligament (OALL) occasionally leads to dysphagia by the anterior osteophyte. A recent report explained that the dysphagia after an occipito-cervical fusion is caused by the narrowing of pharyngeal space due to the cranio-cervical malalignment. The purpose of this study was to evaluate the cranio-cervical alignment in patients with OALL complaining of the dysphagia. Subjects and methods: The subjects were 11 cases with complaining of dysphagia due to cervical OALL who underwent anterior cervical OALL resection and as control, age-matched 12 cases without dysphagia who have diffuse idiopathic skeletal hyperostosis in cervical spine. All subjects were male, and the mean age was 59.5 ± 9.1 years. The subjects were divided into two groups according to the symptoms of dysphagia (dysphagia, group A; control, group B). The O–C2 angle, C2–C7 angle, and the maximum thickness of OALL and the cranio-cervical alignment (pharyngeal inlet angle; PIA) and swallowing line (S-line) were measured before and after the operation on the lateral cervical radiogram at the sitting position. Results: Group A showed significantly large maximum thickness of OALL, small cervical range of motion, small O–C2 angle, large C2–C7 angle, and small PIA. The S-line crossed the anterior apex of cervical osteophyte in group A. After OALL resection, dysphagia had improved, PIA had increased, and the S-line uncrossed the apex of cervical vertebrae in all cases. Conclusion: The prevalence of dysphagia in patients with cervical OALL was influenced by the thickness of osteophyte, cervical mobility, and cranio-cervical alignment.